Seqüestro e variação geográfica dos alcalóides na defesa química de Melanophryniscus simplex (Caramaschi e Cruz, 2002) (Anura, Bufonidae) - Colombo, Patrick (2012)
Red bellied toads of the genus Melanophryniscus occur in southern South America and represent one of several lineages of anurans with the ability to sequester defensive alkaloids from a diet of alkaloid-containing arthropods and are presumably used as a chemical defense against predators, parasites and pathogens. The alkaloid diversity present in alkaloid-containing frogs may vary geographically among populations as well as among individuals of the same population. This variation appears to be associated with differences in the availability of alkaloid-containing arthropods at different locations. Aspects of chemical defense in alkaloid containg frogs has been well documented in dendrobatid and mantellid frogs, but less so in Melanophryniscus. Herein we show new data about chemical defense in Melanophrynicus. This thesis is organized in four articles. In the first arfticle we present data on the geographic and individual variation of Melanoprhyniscus simplex. The second show new information about the environmental distribuition of the alkaloids of M. simplex, comparing samples os soil invertebrates and frogs. The third paper brings some data about the variation on alkaloid diversity between females and males of M. simplex. And the fourth article presents new information about the presence of alkaloids in non-integumentary tissues of alkaloid-containg frogs.